Ireland and India : nationalism, empire and memory - Silvestri, Michael, 1966- (Cambridge imperial and post-colonial studies series., 2009)
"This book examines the imaginative dimension of Irish-Indian imperial connections in the late nineteenth and twentieth centuries by considering the relationships between Irish and Indian nationalists, the construction of Irishmen as British imperial heroes, and Irish nationalist commemoration of the mutiny of a regiment of Irish soldiers in India"--Provided by publisher.